Unmanned Six-Wheels Bogie Rover with Robotic Arm for Surveillance and Fixing Objects - et. al., Vishnu Vardhan Battu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wheeled mobile robots’ utilization is increased rapidly and in dangerous situation such as planetary surface exploration. This paper provides a manner to construct a mobile controlled six-wheels Rover with robotic arm and camera which can stream video over internet. This project is controlled by blynk custom designed mobile application. With robotic arm can collect samples from the affected area.